Treatment of rat thyrocytes in vitro with cathepsin B and L inhibitors results in disruption of primary cilia leading to redistribution of the trace amine associated receptor 1 to the endoplasmic reticulum - Szumska, Joanna (Biochimie, 2019)
Taar1 is a G protein-coupled receptor (GPCR) confined to primary cilia of rodent thyroid epithelial cells. Taar1-deficient mouse thyroid follicles feature luminal accumulation of thyroglobulin suggesting that Taar1 acts as a regulator of extra- and pericellular thyroglobulin processing, which is mediated by cysteine cathepsin proteases present at the apical plasma membrane of rodent thyrocytes. Here, by immunostaining and confocal laser scanning microscopy, we demonstrated co-localization of cathepsin L, but only little cathepsin B, with Taar1 at primary cilia of rat thyrocytes, the FRT cells. Because proteases were shown to affect half-lives of certain receptors, we determined the effect of cathepsin activity inhibition on sub-cellular localization of Taar1 in FRT cells, whereupon Taar1 localization altered such that it was retained in compartments of the secretory pathway. Since the same effect on Taar1 localization was observed in both cathepsin B and L inhibitor-treated cells, the interaction of cathepsin activities and sub-cellular localization of Taar1 was thought to be indirect. Indeed, we observed that cathepsin inhibition resulted in a lack of primary cilia from FRT cells. Next, we proved that primary cilia are a necessity for Taar1 trafficking to reach the plasma membrane of FRT cells, since the disruption of primary cilia by treatment with β-cyclodextrin resulted in Taar1 retention in compartments of the secretory pathway. Furthermore, in less well-polarized rat thyrocytes, namely in FRTL-5cells lacking primary cilia, Taar1 was mainly confined to the compartments of the secretory pathway. We conclude that Taar1 localization in polarized thyroid epithelial cells requires the presence of primary cilia, which is dependent on the proteolytic activity of cysteine cathepsins B and L.
Gesehen am 27.11.2019